Effects of nitrogen forms on the growth, ascorbateglutathione cycle and lipid peroxidation in developing seeds of vegetable soybean - Lei Chen; Si-Chen Liu; Jun-Yi Gai; Yue-Lin Zhu; Li-Fei Yang; Guo-Ping We (Global Journal of Food and Agribusiness Management, 2018)
A pot culture experiment of nitrogen forms (NO3 ¯ :NH 4 + ) with four ratios (100:0, 75:25, 50:50, and 25:75) in nutrient solutions was conducted to examine the effects of nitrogen forms on the growth, ascorbate-glutathione (ASC-GSH) cycle and lipid peroxidation in developing seeds of vegetable soybean. Results showed that the best plant growth vigor was observed in NO3 ¯ (75%), and then in NH4 + (50%). The contents of ASC and dehydroascorbate (DHA), and DHA/ASC ratio in NO 3 ¯ (75%) and NH4 + (50%) maintained stable values, but obvious increases were observed in NO 3 ¯ (100%) and NH4 + (75%). The GSH contents exhibited increasing trends, while the increases in oxidized glutathione (GSSG) contents were only observed in NO3 ¯ (100%) and NH4 + (75%), in which high GSSH/GSH ratios were observed. In NO3 ¯ (100%) and NH4 + (75%), the enzymes activities in ASCGSH cycle, including ascorbate peroxidase (APX, EC 1.11.1.11), dehydro -ascorbate reductase (DHAR, EC 1.8.5.1) and glutathione reductase (GR, EC 1.6.4.2), expressed increasing trends. Significant increases in lipid peroxidation and hydrogen peroxide (H2O 2) generation were also observed in NO3 ¯ (100%) and NH4 + (75%) as against NO 3 ¯ (75%) and NH4 + (50%). It was shown that the degree of oxidative damage was relatively low when the ratio of nitrogen forms was 75:25, and this could be a good guidance on the nitrogen application in the cultivation of vegetable soybean.